FGF8, FGF10 and FGF receptor 2 in foreskin of children with hypospadias: an analysis of immunohistochemical expression patterns and gene transcription. Issue 1 (February 2020) - Haid, Bernhard; Pechriggl, Elisabeth; Nägele, Felix; Dudas, Jozsef; Webersinke, Gerald; Rammer, Melanie; Fritsch, Helga; Oswald, Josef
Summary: Introduction: Fibroblast growth factors (FGFs) play a crucial role in early embryogenesis of the genital tubercle and are involved in the development of hypospadias, affecting both endo- and ectodermally derived tissues. It was hypothesized that expression of FGFs could be qualitatively or quantitatively altered in skin of children with hypospadias. Objective: The objective of the study was to investigate expression patterns and transcription levels of FGF8, FGF10, and FGF Receptor 2 (FGFR2) in patients with hypospadias compared to normal controls. Patients and methods: Skin samples from the ventro-lateral aspect of the foreskin of 32 patients with hypospadias (17 distal and 15 proximal, mean age 25 months) and 10 normal foreskin samples (mean age 77 months) were analyzed by immunohistochemistry. Staining, localization, and distribution of positive cells in epidermis and dermis were categorized independently by two researchers. Complementary DNA (cDNA) samples prepared from messenger RNA (mRNA) isolates of the same samples were analyzed by quantitative polymerase chain reaction (qPCR), comparing expressions of FGF8, FGF10, and FGFR2 with loading controls. Results: Patients with hypospadias consistently showed aberrant immunohistochemical staining patterns for FGF8/FGF10/FGFR2 in epidermis and dermis compared to patients without penile malformation (p < 0.01 for all markers). qPCR displayed no difference in expression levels on mRNA level ( FGFR2 p = 0.44, FGF8 p = 0.77, and FGF10 p = 0.17) comparing normal foreskin with foreskin from patients with hypospadias. Figure. Discussion: The results point at an impact of FGF signaling during embryological development of hypospadias on skin, as an ectodermally derived tissue. Similar to the urethral development, this might be a result of mesothelial–epithelial interactions. The differing expression patterns in immunohistochemistry are not matched by a quantitative difference in marker expression on the mRNA level, putatively caused by post-translational modifications or alterations of the downstream pathway. FGFs, particularly FGF10 and FGFR2, are critically involved in wound healing. Conclusions: There are significant differences in localization and distribution of FGF8, FGF10, and FGFR2 in comparisons of normal foreskin to foreskin of patients with hypospadias, whereas there is no difference in the quantitative expression of these markers on the mRNA level. This confirms the notion that penile skin is affected as well by the embryological aberrations during the embryogenesis of hypospadias. Summary Figure Distribution of different FGF expression patterns in percent according to pathology (distal and proximal hypospadias) vs controls (normal foreskin). A, FGFR2; B, FGF8; C, FGF10; and D, schematic drawing of patterns identified in epidermis and dermis. Figure